PENENTUAN HARGA OPSI COMPOUND CALL ON CALL EROPA - , ROBBI HABIBI; , Dr. Abdurakhman, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In stock and options trading, stock price movements are often up and down. This raises concerns investor to invest in the financial sector. European Call on Call Compound Option is a option on the option. European Call on Call Compound Options will protect and minimize the loss of the option holder if the stock price falls below the market price of the contract. This thesis will discuss the option price calculation Compound Call on Call Europe with the Black-Scholes model approach and the bivariate normal distribution.